Cardiovascular Disease is Associated with COPD Severity and Reduced Functional Status and Quality of Life. (1st September 2014) - Black-Shinn, Jennifer L.; Kinney, Gregory L.; Wise, Anastasia L.; Regan, Elizabeth A.; Make, Barry; Krantz, Mori J.; Barr, R. Graham; Murphy, James R.; Lynch, David; Silverman, Edwin K.; Crapo, James D.; Hokanson, John E.; et al.
Abstract: Introduction: Smoking is a major risk factor for both cardiovascular disease (CVD) and chronic obstructive pulmonary disease (COPD). More individuals with COPD die from CVD than respiratory causes and the risk of developing CVD appears to be independent of smoking burden. Although CVD is a common comorbid condition within COPD, the nature of its relationships to COPD affection status and severity, and functional status is not well understood. Methods: The first 2, 500 members of the COPDGene cohort were evaluated. Subjects were current and former smokers with a minimum 10 pack-year history of cigarette smoking. COPD was defined by spirometry as an FEV1 /FVC < lower limit of normal (LLN) with further identification of severity by FEV1 percent of predicted (GOLD stages 2, 3, and 4) for the main analysis. The presence of physician-diagnosed self-reported CVD was determined from a medical history questionnaire administered by a trained staff member. Results: A total of 384 (15%) had pre-existing CVD. Self-reported CVD was independently related to COPD (Odds Ratio = 1.61, 95% CI = 1.18–2.20, p = 0.01) after adjustment for covariates with CHF having the greatest association with COPD. Within subjects with COPD, pre-existing self-reported CVD placed subjects at greater risk of hospitalization due to exacerbation, higher BODE index, and greater St. George's questionnaire score. The presence of self-reported CVD was associated with a shorter six-minute walk distance in those with COPD ( p < 0.05). Conclusions: Self-reported CVD was independently related to COPD with presence of both self-reported CVD and COPD associated with a markedly reduced functional status and reduced quality of life. Identification of CVD in those with COPD is an important consideration in determining functional status.